DISSERTATION TITLE: THERMAL AND SURFACE INTEGRITY STUDY OF AZ31C MAGNESIUM ALLOY INFLUENCED BY CRYOGENIC TURNING MACHINING PROCESS - ., MOHD DANISH (2018)
The use of lightweight metal alloy is highly encouraging because low weight requires less power and hence minimizes the harmful emission of gases. Magnesium alloys are superseding in this category because of their high strength to weight ratio.